1987
DOI: 10.1002/pssa.2211030214
|View full text |Cite
|
Sign up to set email alerts
|

Low Temperature Thermal Expansion of InP

Abstract: The temperature dependence of the lattice constant of InP monocrystals is measured within the interval of 13 to 300 K. Coefficients of thermal expansion are calculated and compared with results of other authors. Thermal expansion becomes negative below 64 K in accordance with general lattice dynamical considerations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
1
8
1
Order By: Relevance
“…As to the function α th (T ), it was measured by various authors, see Refs. [41][42][43]. We follow the measurements of Haruna et al 41 , which basically agree with those of other authors but are more complete.…”
Section: Inpsupporting
confidence: 88%
“…As to the function α th (T ), it was measured by various authors, see Refs. [41][42][43]. We follow the measurements of Haruna et al 41 , which basically agree with those of other authors but are more complete.…”
Section: Inpsupporting
confidence: 88%
“…It is seen that the general agreement between the present theoretical calculations and the experimental measurements is quite good for these compounds. From the principles of thermodynamics, it is known that the linear thermal expansion coefficient should approach zero as T closes to 0 K. However, the measured results for GaSb [48] and InP [49] are divergent near 0 K. It is suggested that new measurements are worthwhile to confirm our result for GaSb at ultralow temperature.…”
Section: Linear Thermal Expansion Coefficientcontrasting
confidence: 43%
“…A numerical list of these thermal expansion coefficients is given in Table 2. For a quantitatively evaluation, we compared present results with a few reports from experimental measurement for AlN [46], BP [46], GaAs [47], GaSb [48], InP [49,50] and GaP [46,51] rameters for most of the other III-V phases are still unavailable. These comparisons for AlN, GaSb, InP, and GaP are presented in Fig.…”
Section: Linear Thermal Expansion Coefficientmentioning
confidence: 91%
“…Figure 2 shows the energies of the bulk InP G 1c and X 1c conduction states vs lattice constant a, exhibiting a crossing at a 5.5852 Å; the deformation relative to the LDA calculated zero-pressure lattice constant (at which our pseudopotential is generated) is Da͞a 0.0414. The measured [5] bulk Da͞a 0.0370 corresponding to a transition pressure [5] of 112 kbar is within 10% (Table I [ 5,16]). Figure 3 shows the energies of three lowest conduction states of P-centered InP dots vs lattice constant near the critical transition point.…”
Section: Huaxiang Fu and Alex Zungermentioning
confidence: 94%